Thermal Economy Optimization of Distributed Energy System Combining Cooling, Heating and Power Based on Genetic Algorithm - Weiting Yue, Zhongjie He, Xiyou Zhou (Forest Chemicals Review, 1970)
Optimization of the installed capacity and annual operating hours is one of the valid methods of improving energy efficient and economy performance of distributed energy system. Firstly, a hotel building thermodynamic system combined cooling, heating and power (CCHP) was proposed, which based on the annual energy demand. Multi-object optimization model of CCHP was established by means of combining exergy quantity, construction budget and economic returns. And then, Optimum power, energy supply and annual hours were calculated by adopting Fast- Elitist-Non-Dominated-Sorting-Generic-Algorithm(NSGA). Finally, the effects of the prices of different energy were compared and principles of installation and operation were analyzed.